IDENTIFIKASI MINERAL BIJIH BESI DENGAN MENGGUNAKAN METODE INDUCED POLARIZATION (IP) DI DAERAH OKU SELATAN, SUMATERA SELATAN - Muhammad Nafian S.Si; Tati Zera, M.Sc; Wildan Cahara bg, ST. (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
To find out the potential of hematite in Pulau Beringin, the data analyzing must be done thoroughly towards the hematite on the surface of the soil by doing the Geolistric method. Geolistric method is a Geophysic’s method that learns about the characteristics of electricity inside the earth and detect them on the surface of earth. One of the methods in Geolistric is Induce Polarization (IP), which is the process of electric polarization that can be used to identify areas containing the hematite. The measurement result of 8 strips, anomaly IP can only be found in strip K. , that shown at point K.17 with chargeability value 60mdt, meanwhile the resistivity value at point K.17 is 30 Ωm, that contain shale and granite. Moreover, this result doesn’t identify the existence of hematite in the strip due to lack of chargeability and resistivity value in the other strips. Keywords: Geolistric method, Induced Polarization (IP).